Development of a School Profile Website as a Digital Information Medium Using the Waterfall Method - Muhammad Mustakim; Sofiansyah Fadli; Ahmad Tantoni (Universitas Trilogi, 2026)
The development of information technology encourages educational institutions to utilize digital media in delivering information more effectively. However, SMPN 4 Praya Tengah still uses conventional methods in disseminating information, resulting in limited reach and inefficiency. This study aims to design and implement a school profile website as a digital information medium that can be widely accessed by students, parents, and the community. The method in this study uses the Waterfall model, which was selected due to its systematic and structured development stages that are well-suited for projects with clearly defined and stable requirements. The Waterfall model includes the stages of analysis, design, implementation, and testing. This research integrates PHP and JavaScript programming languages with a MySQL database. The resulting system provides comprehensive features ranging from school profile, vision and mission, news, announcements, gallery, to online admission services (PPDB). The website is designed with a simple and user-friendly interface so it can be well managed by the school. Through Black Box Testing, this website has been proven to function optimally in presenting information accurately and in a structured manner. System validation was conducted through two methods: Black Box Testing, which confirmed all features operate according to specifications, and User Acceptance Testing (UAT) involving 50 respondents with 16 evaluation items, yielding an average score of 78.50% (categorized as 'Agree'). These results empirically validate that the implementation of this website provides measurable benefits in improving the effectiveness of information delivery, expanding access, and supporting digital transformation within the school environment. This system is expected not only to facilitate digital transformation in schools but also to serve as a reference for the development of other school websites.